Latihan Shuttle Run dalam Meningkatkan Kelincahan Dribbling Siswa Ekstrakurikuler Sepak Bola - rangga, rangga; Aryanti, Silvi; Destriana, Destriana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This study aims to determine the effect of shuttle run training on dribbling results in extracurricular soccer students at SMP Negeri 29 Palembang. The method used in this study is experimental. The research design used was the One Group Pretest-Posttest Design. This sample was taken using a total population sampling technique with a total sample of 30 students. The instrument of this research is the test of dribbling. From the results of data processing and analysis using the data normality test, homogeneity test and hypothesis test using the T test formula, it was found that shuttle run training alone had an effect on improving dribbling results in soccer games. This can be seen from the results of data analysis using the t test formula calculation with the calculated t criterion being greater than t table (13.730 ˃ 1.70) with a confidence level of 0.95 (α = 0.05) and the number of samples (N = 30). Conclusion, is that shuttle run training alone has an influence on improving dribbling results in extracurricular soccer students at SMP Negeri 29 Palembang. Keyword : Dribbling, Football, Shuttle Run